(untitled) (Damascus University Journal for engineering sciences, 2021)
3D models of archaeological finds (such as statues) and architectural structures are very important in order to study, analyze and also to reconstruct and document these finds and structures. The visualization of these models allows the user to get the photo realistic impression for these finds and structures rather than graphics-based presentation. 3D visualization has many applications in the field of archeology, art history, architecture, civil engineering, tourism, etc. From precision point of view, traditional field survey of architectural structures is better than photogrammetric documentation. With regard to archaeological finds, 3D laser scanning is the perfect solution because of the high density of scanned points. But these solutions are expensive in terms of time and needs. Therefore, we propose in this study the use of a low cost photogrammetric system for precise 3D modeling and visualization of archaeological finds (such as statues) and buildings. This system is composed of an ordinary digital camera (not designed for photogrammetric purposes), simple control data and a software for orientation and modeling. The effective use of this system require the application of some simple rules which are presented in this study.